An improved fruit transcriptome and the identification of the candidate genes involved in fruit abscission induced by carbohydrate stress in litchi - Li, Caiqin; Wang, Yan; Huang, Xuming; Li, Jiang; Wang, Huicong; Li, Jianguo (Frontiers in Plant Science, 2015)
Massive young fruit abscission usually causes low and unstable yield in litchi (Litchi chinensis Sonn.), an important fruit crop cultivated in tropical and subtropical areas. However, the molecular mechanism of fruit drop has not been fully characterized. This study aimed at identification of molecular components involved in fruitlet abscission in litchi, for which reference genome is not available at present. An improved de novo transcriptome assembly was firstly achieved by using an optimized assembly software, Trinity. Using improved transcriptome assembly as reference, digital transcript abundance (DTA) profiling was performed to screen and identify candidate genes involved in fruit abscission induced by girdling plus defoliation (GPD), a treatment significantly decreased the soluble sugar contents causing carbohydrate stress to fruit. Our results showed that the increasing fruit abscission rate after GPD treatment was associated with higher ethylene production and lower glucose levels in fruit. A total of 2,771 differentially expressed genes were identified as GPD-responsive genes, 857 of which were defined by GO and KEGG enrichment analyses as the candidate genes involved in fruit abscission process. These genes were involved in diverse metabolic processes and pathways, including carbohydrate metabolism, plant hormone synthesis and signaling, transcription factor activity and cell wall modification that were rapidly induced in the early stages (within 2 d after treatment). qRT-PCR was used to explore the expression pattern of 15 selected candidate genes in the abscission zone, pericarp and seed, which confirmed the accuracy of our DTA data. More detailed information for different functional categories was also analyzed. This study profiled the gene expression related to fruit abscission induced by carbohydrate stress at whole transcriptome level and thus provided a better understanding of the regulatory mechanism of young fruit abscission in litchi.